Phylogeny and description of Eknomia, a morphologically unusual new genus of Neotropical Cryptinae (Hymenoptera, Ichneumonidae), with three new species - Santos, Bernardo F.; Aguiar, Alexandre P. (Zootaxa, 2012)
The Cryptini Eknomia Santos et Aguiar gen. nov. is proposed, described, and cladistically compared with representativespecies of 40 outgroup genera from twelve cryptine subtribes. A total of 98 morphological characters were evaluated. Allanalyses, conducted in TNT under implied and equal weighting, clearly suggest that Eknomia is a monophyletic groupand can be treated as a distinct genus. Its likely sister group, however, varied among different analyses and could not beascertained. The relationships of the new genus are therefore unclear, and because of this it is not assigned to any of thecurrently recognized subtribes. Eknomia can be diagnosed mainly by the anterior transverse carina of propodeum entirelyabsent; propodeum more or less uniformly strigate; clypeus almost entirely flattened; ovipositor stout, with compressed,minutely serrate flange at apex of dorsal valve, subapically crossed by a subvertical line; first metasomal spiracle placedat tergite midlength or nearly so; and hind margin of metanotum with tooth-like projections. The species E. nigra Santoset Aguiar, sp. nov., E. rubra Santos et Aguiar, sp. nov. and E. propodeator Santos et Aguiar, sp. nov. are described and illustrated. The genus is recorded from Colombia to southern Brazil.